2021
DOI: 10.3389/fvets.2021.652479
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Plasma Cytokines, Angiopoietin-2, and C-Reactive Protein in Dogs With Gastric Dilatation Volvulus

Abstract: Background: The degree of systemic inflammation, reperfusion injury and endothelial activation are potentially important determinants of clinical outcomes in dogs with gastric dilatation volvulus (GDV).Objective: To evaluate plasma concentrations and kinetics of inflammatory markers in dogs with GDV over a time frame of 48 h, and to compare to healthy dogs.Design and Setting: Prospective, observational cohort study in client-owned dogs with GDV.Materials and Methods: Fifteen dogs with GDV and 9 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 51 publications
0
18
1
Order By: Relevance
“…Exclusion criteria were known history of kidney disease and administration of nephrotoxic drugs (such as non-steroidal analgesic drugs) within 14 days before inclusion in the study. Some data from the dogs in the non-lidocaine group were used in a previous study (9). Additionally, 18 healthy dogs, which were part of a previous study, served as a healthy control group for pCr, uNGAL and UNCR (23).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria were known history of kidney disease and administration of nephrotoxic drugs (such as non-steroidal analgesic drugs) within 14 days before inclusion in the study. Some data from the dogs in the non-lidocaine group were used in a previous study (9). Additionally, 18 healthy dogs, which were part of a previous study, served as a healthy control group for pCr, uNGAL and UNCR (23).…”
Section: Subjectsmentioning
confidence: 99%
“…All GDV dogs underwent standardized stabilization, anesthesia, surgery, and post-operative monitoring as described in a previous study by the same institution (9). For cardiovascular stabilization, supplemental oxygen and IV isotonic balanced and buffered crystalloids (Plasma-Lyte A R , Baxter AG, Switzerland) was administered at the clinician's discretion.…”
Section: Interventions General Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP also dropped to the greatest extent in dogs who died, rather than in survivors. In dogs with gastric dilatation, gastric volvulus and urolithiasis CRP was within the normal range, but other authors report a significant increase in CRP concentration 24 and 48 h after the gastric dilatation-volvulus surgery [ 98 ]. Thus, it may be concluded that CRP increases with the severity of the condition, although the rapid decrease over a short time may carry a negative prognostic value and should be taken into consideration by clinicians as well as researchers.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Hepatocytes produce CRP when stimulated by pro‐inflammatory cytokines such as interleukin‐6 (IL‐6), tumour necrosis factor‐alpha (TNF‐α) and interleukin‐1‐beta (IL‐1β) 7 . Within the first 24–48 hours of tissue injury, serum CRP (sCRP) increases in response to stimulus before quickly declining and normalising within 8 days 6–10 . In veterinary medicine, sCRP has been shown to be elevated in numerous conditions, such as pyometra, acute pancreatitis, some neoplasias (such as lymphoma) and immune‐mediated diseases (such as steroid‐responsive meningitis‐arteritis) 5,11–15 …”
Section: Introductionmentioning
confidence: 99%